Rehabilitation of Notary Offices After Cancellation of Dishonorable Dismissal In Protection of Notary Rights - Nisrina Putri Rizkya Nugroho; Arif Zainudin; R. Imam Rahmat Sjafi'i (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Indonesia, as a country governed by the rule of law, places law as the foundation for governance and the protection of citizens' rights. In ensuring legal certainty for various legal acts, notaries play a crucial role as public officials authorized to issue authentic deeds. However, in practice, notaries can be subject to administrative sanctions, including dishonorable dismissal, if they violate their obligations and prohibitions as stipulated in laws and regulations. Problems arise when the decision to dishonorably dismiss is subsequently overturned by the court, while the prevailing regulations do not clearly regulate the mechanism for rehabilitation of notaries. This situation creates a legal vacuum that has the potential to lead to legal uncertainty and the failure to protect the rights of injured notaries. This study aims to analyze the legal provisions regarding dishonorable dismissal of notaries and formulate appropriate regulations regarding rehabilitation of notaries upon the cancellation of such dismissal decisions. The research method used is normative legal research with a statutory, conceptual, and case-based approach. The legal materials used include laws and regulations, legal doctrine, and court decisions, particularly Supreme Court Decision Number 294 K/TUN/2021. The research results show that although the Indonesian legal system has provided legal protection mechanisms through administrative remedies and lawsuits to the State Administrative Court, there are no regulations that explicitly regulate the rehabilitation of a Notary's position after the revocation of a dishonorable dismissal decision. Therefore, regulations are needed that explicitly regulate the rehabilitation mechanism for a Notary's position, including restoration of a Notary's good name, reinstatement as a Notary, restoration of the right to practice, and the return of other administrative rights to ensure legal certainty and the protection of Notary's rights.